2015
DOI: 10.1021/acs.nanolett.5b00996
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion-Based Dynamic Magnonic Crystal

Abstract: A linear array of periodically spaced and individually controllable skyrmions is introduced as a magnonic crystal. It is numerically demonstrated that skyrmion nucleation and annihilation can be accurately controlled by a nanosecond spin polarized current pulse through a nanocontact. Arranged in a periodic array, such nanocontacts allow the creation of a skyrmion lattice that causes a periodic modulation of the waveguide's magnetization, which can be dynamically controlled by changing either the strength of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 81 publications
2
126
0
1
Order By: Relevance
“…The magnetic skyrmion can also be nucleated with the nano-patterning 39 and be converted from a domain-wall pair 25 . For the manipulation of the magnetic skyrmion, one can use the spin current 21,23 , the spin wave [40][41][42][43] , as well as the thermal gradient [44][45][46] to drive the magnetic skyrmion.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic skyrmion can also be nucleated with the nano-patterning 39 and be converted from a domain-wall pair 25 . For the manipulation of the magnetic skyrmion, one can use the spin current 21,23 , the spin wave [40][41][42][43] , as well as the thermal gradient [44][45][46] to drive the magnetic skyrmion.…”
Section: Introductionmentioning
confidence: 99%
“…The injection of a skyrmion with a perpendicular current is not covered here, because it has already been numerically delivered in refs. 19,30,50 . Subsequently, we will examine successively the motion dynamics of a skyrmion, a DW pair, and the coexisting skyrmion and DW pair triggered by an in-plane current.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from these intriguing features, i.e., the flexibility around defects and the high sensitivity to currents, recently, it was established that moving magnetic skyrmions can bring about an emergent electromagnetic field, 15 and most recently, it was demonstrated that magnetic skyrmions can even be controllably written and erased using a tiny mechanical force exerted by a microtip. 21 Because of these merits, magnetic skyrmions serve as an active platform for searching new phenomena 20,[22][23][24][25] and more importantly as a promising object for building functional devices 18,[26][27][28][29][30][31][32][33] . Compared to conventional DWs, chiral DWs show greatly enhanced mobility owing to the combined action of the DMI and the spin-Hall effect, and thus hold great promise for implementing new families of spintronic devices.…”
Section: Skyrmionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been tremendous interest in magnetic skyrmions due to their unusual spintronic properties, such as their topological stability which protects them from being hindered by defects [19][20][21] and their current-driven motion with an ultralow depinning threshold current [21][22][23]. In view of these distinct features, magnetic skyrmions are promising candidates for information carriers in a range of applications in spintronics such as race-track memory devices [20,21], skyrmion logic devices [24], or skyrmion magnonic devices [25], so understanding how to systematically control skyrmion configurations and dynamics with nanopatterns has broad relevance. Although numerous efforts have been devoted to manipulating skyrmion motion, there is little work on how to precisely control their position and confinement.…”
Section: Introductionmentioning
confidence: 99%